2013
DOI: 10.1080/13691058.2012.763186
|View full text |Cite
|
Sign up to set email alerts
|

Black gay men as sexual subjects: race, racialisation and the social relations of sex among Black gay men in Toronto

Abstract: In this study of Black gay and bisexual men in Toronto, sexually active survey participants reported on their sexual behaviours with male partners of different ethnoracial backgrounds, and interview participants reflected on how their sexual relationships emerged in the context of race and interracial desire. Most survey participants reported sexual relationships with other Black men. Participants were more likely to be insertive with White and other ethnoracial men than with Black men. A significant number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
7

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 18 publications
0
22
0
7
Order By: Relevance
“…Research has found that racial minority MSM report being frequent targets of sexual objectification, which is characterized by assumed negative or positive sexual characteristics based on race (Husbands et al, 2013; Paul, Ayala, & Choi, 2010; Stokes & Peterson, 1998; Wilson et al, 2009; Wilson & Yoshikawa, 2004). A recent qualitative study of a racially-diverse sample of MSM found that individuals held various race-based sexual stereotypes with regard to potential partners' sexual characteristics, gender expectations, and sexual role preferences (Wilson et al, 2009).…”
mentioning
confidence: 99%
“…Research has found that racial minority MSM report being frequent targets of sexual objectification, which is characterized by assumed negative or positive sexual characteristics based on race (Husbands et al, 2013; Paul, Ayala, & Choi, 2010; Stokes & Peterson, 1998; Wilson et al, 2009; Wilson & Yoshikawa, 2004). A recent qualitative study of a racially-diverse sample of MSM found that individuals held various race-based sexual stereotypes with regard to potential partners' sexual characteristics, gender expectations, and sexual role preferences (Wilson et al, 2009).…”
mentioning
confidence: 99%
“…preference; Box B) and the sexual scripts that allow for sexual positioning and/or condom negotiation ability within the sexual encounter (Box D). This model also considers individual and partner age and race/ethnicity within these distal and proximal forces as sexual identity and negotiation ability change with age and proximal power dynamics likely vary within and between different ethnic groups of MSM (Bowleg, 2004; Han, 2008; Husbands et al, 2013; Malebranche & Bryant, 2005). Sexual positioning identities and preferences guide the power dynamics present within the sexual encounter (Box C), which has a cyclical relationship with sexual positioning and condom use, implicated in the latitude an individual has to negotiate risk reduction behaviors (Box D).…”
Section: Discussionmentioning
confidence: 99%
“…Gagnon and Simon’s (1984) theory of sexual scripting highlights that sexual interactions can be informed by sexual ‘scripts’ derived from cultural scenarios, interpersonal interactions, and intrapersonal characteristics that frame the way people experience different sexual interactions. Masculinity stereotypes may create cues that could be an important precursor to sexual scripts between men and may manifest differently for MSM and MSMW (Husbands et al, 2013; Lick & Johnson, 2015). From our review, it is unclear how sexual scripts may differ for MSM compared to MSMW or how the cultural meanings and values behind masculinity may affect sexual position decision-making within sub-cultures of MSM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations